2015
DOI: 10.1111/dom.12438
|View full text |Cite
|
Sign up to set email alerts
|

New insulin glargine 300 U/ml compared with glargine 100 U/ml in insulin‐naïve people with type 2 diabetes on oral glucose‐lowering drugs: a randomized controlled trial (EDITION 3)

Abstract: AimsTo compare the efficacy and safety of new insulin glargine 300 U/ml (Gla-300) with that of glargine 100 U/ml (Gla-100) in insulin-naïve people with type 2 diabetes using oral glucose-lowering drugs.MethodsThe EDITION 3 study was a multicentre, open-label, parallel-group study. Participants were randomized to Gla-300 or Gla-100 once daily for 6 months, discontinuing sulphonylureas and glinides, with a dose titration aimed at achieving pre-breakfast plasma glucose concentrations of 4.4–5.6 mmol/l (80–100 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

41
488
9
10

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 279 publications
(548 citation statements)
references
References 22 publications
(35 reference statements)
41
488
9
10
Order By: Relevance
“…This finding was accompanied by a lower risk of nocturnal confirmed (≤3.9 mmol/L [≤70 mg/dL]) or severe hypoglycaemia with Gla‐300 than Gla‐100, which was not influenced by renal function. Hence, overall, the pooled results presented here are consistent with the individual EDITION studies,14, 15, 16 which also reported similar glycaemic control and reduced risk of hypoglycaemia with Gla‐300 compared with Gla‐100. Importantly, however, these data show that this advantage of Gla‐300 over Gla‐100 was maintained in people with T2DM and impaired renal function.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This finding was accompanied by a lower risk of nocturnal confirmed (≤3.9 mmol/L [≤70 mg/dL]) or severe hypoglycaemia with Gla‐300 than Gla‐100, which was not influenced by renal function. Hence, overall, the pooled results presented here are consistent with the individual EDITION studies,14, 15, 16 which also reported similar glycaemic control and reduced risk of hypoglycaemia with Gla‐300 compared with Gla‐100. Importantly, however, these data show that this advantage of Gla‐300 over Gla‐100 was maintained in people with T2DM and impaired renal function.…”
Section: Discussionsupporting
confidence: 88%
“…Insulin glargine 300 U/mL (Gla‐300), a second‐generation basal insulin, provides a more stable and prolonged pharmacokinetic and pharmacodynamic profile compared with insulin glargine 100 U/mL (Gla‐100) 13. Data from the phase III EDITION 1, 2 and 3 clinical trials showed that over 6 months, Gla‐300 provided similar glycaemic control to Gla‐100 in participants with T2DM, with less hypoglycaemia 14, 15, 16. Given the reduced hypoglycaemia risk with Gla‐300 vs Gla‐100, we were interested to see if this benefit persisted in individuals with impaired renal function.…”
Section: Introductionmentioning
confidence: 99%
“…The risk of any confirmed or severe hypoglycaemia was lower with IGlarU300 over the 6-month treatment period (RR 0.76 [95% CI 0.59 to 0.99]). 27 EDITION JP2, focusing on Japanese subjects, showed a similar decline in HbA1c over 6 months with no differences observed in changes from baseline and fasting plasma glucose or in the percentage of patients reaching the HbA1c target of less than 7%. Hypoglycaemia was lower, particularly in the first 8 weeks of the study.…”
Section: Studies On U300 Insulinmentioning
confidence: 77%
“…Although IGlarU300 tended to require a higher dose, the weight changes were either comparable or favoured IGlarU300. 25,27 Patients in …”
Section: Studies On U300 Insulinmentioning
confidence: 99%
“…In pharmacokinetics and pharmacodynamics studies, insulin glargine 300 U/mL (Gla-300) has demonstrated low variability in exposure over 24 h, a more consistent activity profile, and prolonged maintenance of glucose control compared with insulin glargine 100 U/mL (Gla-100) [8][9][10]. In the randomized, controlled Phase III EDITION clinical trial program, Gla-300 was shown to be non-inferior to Gla-100 in reducing HbA1c levels, without increasing the risk of hypoglycemia versus Gla-100 in patients with type 1 diabetes (T1D) or T2D at 6 months [11][12][13][14] and at 1 year [15,16]. The proportion of patients who experienced ≥1 confirmed (blood glucose [BG] ≤70 mg/dL) or severe nocturnal hypoglycemic event was significantly lower for Gla-300 than for Gla-100 [17].…”
Section: Introductionmentioning
confidence: 99%